Basicity as a descriptor for catalyst performance: a promoter study for syngas production via autothermal reforming of methane with CO₂ - A. Geetha Bhavani; Sweta Kumari Tripathy; Sachin Sirohi; N. S. Reddy (Clean Technologies and Environmental Policy, 2026)

Fusarium incarnatum Strain K23 Reprograms the Response of Tomato Seedlings to Salt Stress - N. Pallavi; Y. N. Priya Reddy; Geetha Govind; Michael Reichelt; Clabe Wekesa; C. U. Alexandra Furch; Veit Grabe; R. Uma Shaanker; Ralf Oelmüller; Karaba N. Nataraja (Journal of Plant Growth Regulation, 2025)

Microscopical and histochemical assessment of Secamone emetica (Apocynaceae) Leaves -An endemic medicinal plant - Shalini. S; Sudeepthi N; Jayashre. R; Geetha DH (Flora, 2025)

Effects of Metarhizium anisopliae on the histochemistry and enzymatic activities of Helicoverpa armigera (Hübner, 1809) - Yamini R; Shanmugam P.S; Murugan M; Geetha N; Meenakshi P; Srinivasan T; Premalatha K; Kandan A; Sathiyaraj G; Vivekanandhan P (Biocatalysis and Agricultural Biotechnology, 2024)

Chlamydomonas as a model system for studying the relevance of plant genes for their involvement in multiple individual and combined stresses: a study unravelling PgCuZnSOD and PgAPX gene functions - H. M. Mamrutha; Geetha Govind; Hema Ramanna; Radha Sivarajan Sajeevan; A. N. Lokesha; Muthappa Senthil-Kumar; Karaba N. Nataraja (Plant Physiology Reports, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Design and Development of Inexpensive Paper-Based Chemosensors for Detection of Divalent Copper - Mithra Geetha; Kishor Kumar Sadasivuni; Maryam Al-Ejji; Nandagopal Sivadas; Bagmita Bhattacharyya; Farzana N. Musthafa; Sarya Alfarwati; Tamanna Jannat Promi; Sumayya Ali Ahmad; Sara Alabed; Dima Anwar Hijazi; Fatimatulzahraa Alsaedi; et al. (Journal of Fluorescence, 2023)
Simple, portable, and low-cost paper-based sensors are alternative devices that have the potential to replace high-cost sensing technologies. The compatibility of the paper base biosensors for both chemical and biochemical accentuates its feasibility for application in clinical diagnosis, environmental monitoring, and food quality monitoring. High concentration of copper in blood serum and urine is associated with diseases like liver diseases, carcinomas, acute and chronic infections, rheumatoid arthritis, etc. Detection of copper concentration can give an early sign of Alzheimer disease. Apart from that genetic Wilson's disease can be detected by evaluating the concentration of copper in the urine. In view of the above advantages, a novel and the highly sensitive paper-based sensor has been designed for the selective detection of Cu 2+ ions. The fast and highly sensitive chemiresistive multi-dye system sensor can detect Cu 2+ ions selectively in as low as 2.23 ppm concentration. Least interference has been observed for counter ion in the detection of Cu 2+ . Copper chloride, nitrate, and acetate were used to validate the detection process. This assay provides a very high selectivity of Cu 2+ ion over other metal cations such as Na + , Mg 2+ , Ca 2+ , etc. The easy preparation and high stability of dye solutions, easy functionalization of the paper-based sensors, high selectivity over other cations, low interference of counter anion, and significantly low detection limit of 2.23 ppm make it an effective Cu 2+ ion sensor for real-time application in near future. Graphical Abstract

Plant growth promotion and biological control of Sclerospora graminicola in pearl millet by endophytic Streptomyces spp. - H. G. Pushpalatha; J. Naveen; N. Geetha; G. Hithamani; H. Shekar Shetty (Indian Phytopathology, 2023)

Twisted top disease a destructive disease of sugarcane in India - R. Viswanathan; N. Geetha; K. P. Salin; R. Selvakumar; P. Malathi; A. R. Sundar; R. Nithyanantham; K. Manivannan (Indian Phytopathology, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Epidemiology of sugarcane wilt: predisposition by root borer Polyocha depresella a myth or reality - R. Viswanathan; R. Selvakumar; N. Geetha; C. G. Balaji; A. Annadurai; Adhini S. Pazhani; P. Malathi; A. Ramesh Sundar; R. Nithiyanantham; K. Manivannan (Indian Phytopathology, 2022)

Characterisation of an individual of the giant form of the purpleback flying squid Sthenoteuthis oualaniensis (Cephalopoda: Ommastriphidae) in the Arabian Sea and its biological descriptors - Kurichithara K. Sajikumar; Theparambil M. Najmudeen; Nadakkal Ragesh; N. S. Jeena; Summaya Rahuman; K. T. Sadanandan Sunil; Geetha Sasikumar; Kolliyil S. Mohamed (Molluscan Research, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Identification of rice genotypes for seedling stage multiple abiotic stress tolerance - Tinu Thomas; J. Purushothaman; R. Janarthanan; N. Anusuya; Prasanna Geetha Medisetti; J. Karthick; S. Nadaradjan; S. Thirumeni (Plant Physiology Reports, 2020)

Planetary waves in the mesosphere lower thermosphere during stratospheric sudden warming: observations using a network of meteor radars from high to equatorial latitudes - N. Koushik; K. Kishore Kumar; Geetha Ramkumar; K. V. Subrahmanyam; G. Kishore Kumar; W. K. Hocking; Maosheng He; Ralph Latteck (Climate Dynamics, 2020)

Characterization of inertia gravity waves and associated dynamics in the lower stratosphere over the Indian Antarctic station, Bharati (69.4°S, 76.2°E) during austral summers - N. Koushik; Karanam Kishore Kumar; K. V. Subrahmanyam; Geetha Ramkumar; I. A. Girach; M. Santosh; K. Nalini; M. Nazeer; P. R. Shreedevi (Climate Dynamics, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Gold and Silver Nanoparticles Biomimetically Synthesized Using Date Palm Pollen Extract-Induce Apoptosis and Regulate p53 and Bcl-2 Expression in Human Breast Adenocarcinoma Cells - Hussaina Banu; N. Renuka; S.M. Faheem; Raees Ismail; Vinita Singh; Zahra Saadatmand; Saad Sultan Khan; Kavya Narayanan; Alma Raheem; Kumpati Premkumar; Geetha Vasanthakumar (Biological Trace Element Research, 2018)

Simultaneous observations of the quasi 2-day wave climatology over the low and equatorial latitudes in the mesosphere lower thermosphere - Karanam Kishore Kumar; Kandula Venkata Subrahmanyam; Sneha Susan Mathew; N. Koushik; Geetha Ramkumar (Climate Dynamics, 2018)

Evaluation of genetic stability using FRAPD markers as novel method along with antioxidant and anti-diabetic properties of micropropagated Salacia chinensis L. - Majid Bagnazari; M. G. Mahesh; Mehdi Saidi; K. R. Kini; H. S. Prakash; N. Geetha (Acta Physiologiae Plantarum, 2018)

Phycomolecule-coated silver nanoparticles and seaweed extracts induced high-frequency somatic embryogenesis and plant regeneration from Gloriosa superba L. - D. Mahendran; P. B. Kavi Kishor; N. Geetha; P. Venkatachalam (Journal of Applied Phycology, 2018)

Characterization and genome comparison of an Indian isolate of bidensovirus infecting the silkworm Bombyx mori - Tania Gupta; Katsuhiko Ito; Keiko Kadono-Okuda; Geetha N. Murthy; E. Vijaya Gowri; Kangayam M. Ponnuvel (Archives of Virology, 2018)

Proximal Remote Sensing of Herbicide and Drought Stress in Field Grown Colocasia and Sweet Potato Plants by Sunlight-Induced Chlorophyll Fluorescence Imaging - Sadasivan Nair Raji; Geetha Nair Aparna; Changatharayil N. Mohanan; Narayanan Subhash (Journal of the Indian Society of Remote Sensing, 2017)

Effect of phycochemical coated silver nanocomplexes as novel growth-stimulating compounds for plant regeneration of Alternanthera sessilis L. - P. Venkatachalam; S. Malar; M. Thiyagarajan; P. Indiraarulselvi; N. Geetha (Journal of Applied Phycology, 2017)

Climate change projections for Tamil Nadu, India: deriving high-resolution climate data by a downscaling approach using PRECIS - Prasanta Kumar Bal; A. Ramachandran; R. Geetha; B. Bhaskaran; P. Thirumurugan; J. Indumathi; N. Jayanthi (Theoretical and Applied Climatology, 2016)

Detection of OvHV-2 from an outbreak of sheep associated malignant catarrhal fever from crossbred cattle of Southern India - N. Vinod Kumar; B. Sreedevi; A. Karthik; S. Vijaya Lakshmi; A. Geetha Reddy; D. Sreenivasulu (Veterinary Research Communications, 2014)

Longitudinal variations of coral reef features in the Marine National Park, Gulf of Kachchh - J. S. Yogesh Kumar; N. Marimuthu; S. Geetha; Ch. Satyanarayana; K. Venkataraman; R. D. Kamboj (Journal of Coastal Conservation, 2014)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

Activation of autophagic programmed cell death and innate immune gene expression reveals immuno-competence of integumental epithelium in Bombyx mori infected by a dipteran parasitoid - Appukuttan Nair R. Pradeep; Jayaram Anitha; Arvind K. Awasthi; Mohd. A. Babu; Murthy N. Geetha; Hariharan K. Arun; Sagar Chandrashekhar; Guruprasad C. Rao; Nanjappa B. Vijayaprakash (Cell and Tissue Research, 2013)

Expression analysis of drought stress specific genes in Peanut (Arachis hypogaea , L.) - V. Pruthvi; N. Rama; Geetha Govind; Karaba N. Nataraja (Physiology and Molecular Biology of Plants, 2013)

Terrain evaluation through the assessment of geomorphometric parameters using DEM and GIS: case study of two major sub-watersheds in Attapady, South India - V. Prasannakumar; H. Vijith; N. Geetha (Arabian Journal of Geosciences, 2013)

Temporal Trends of Malondialdehyde in Stored Human Plasma - Arun Kumar; B. S. Dhillon; D. N. Rao; Geetha Menon; Hari Shankar; L. K. Dhaliwal; Maiti Leema; Nomita Chandhiok; Neeta Kumar; Rohini Sehgal; Suneeta Mittal; Sumitu Sahdev; et al. (Indian Journal of Clinical Biochemistry, 2012)

Regional Scale Erosion Assessment of a Sub-tropical Highland Segment in the Western Ghats of Kerala, South India - V. Prasannakumar; H. Vijith; N. Geetha; R. Shiny (Water Resources Management, 2011)

Involvement of silicon in pearl millet resistance to downy mildew disease and its interplay with cell wall proline/hydroxyproline-rich glycoproteins - S. Deepak; G. Manjunath; S. Manjula; S. Niranjan-Raj; N. P. Geetha; H. S. Shetty (Australasian Plant Pathology, 2008)

Heterologous expression of Bluetongue VP2 viral protein fragment in Pichia pastoris - T. N. Athmaram; Geetha Bali; Goon G. Kahng; Sulatha Dwarakanath (Virus Genes, 2007)

In vitro clonal propagation through mature nodes of Tinospora cordifolia (Willd.) Hook. F. & Thoms.: An important ayurvedic medicinal plant - A. V. Raghu; S. P. Geetha; Gerald Martin; Indira Balachandran; P. N. Ravindran (In Vitro Cellular & Developmental Biology - Plant, 2006)

Effects of presowing treatments, desiccation and storage conditions on germination of Strychnos nux-vomica seeds, a valuable medicinal plant - V. Sivakumar; R. Anandalakshmi; R. R. Warrier; M. Tigabu; P. C. Odén; S. N. Vijayachandran; S. Geetha; B. G. Singh (New Forests, 2006)

Unsaturated fatty acids from zoospores of Sclerospora graminicola induce resistance in pearl millet - K. N. Amruthesh; N. P. Geetha; H. J. Lyngs Jørgensen; E. de Neergaard; H. Shekar Shetty (European Journal of Plant Pathology, 2005)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

A rapid protocol for somatic embryogenesis from immature leaflets of groundnut (Arachis hypogaea L.) - P. Venkatachalam; P. B. Kavi Kishor; N. Geetha; M. Thangavelu; N. Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 1999)

Antifungal Activity of Some B,D-Seco Limonoids from Two Meliaceous Plants - T. R. Govindachari; G. Suresh; B. Banumathy; S. Masilamani; Geetha Gopalakrishnan; G. N. Krishna Kumari (Journal of Chemical Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

In Vitro selection of groundnut cell lines fromCercosporidium personatum culture filtrates and regeneration of resistant plants through cell culture - P. Venkatachalam; N. Geetha; N. Jayabalan; S. Saravanababu (Journal of Plant Biology, 1998)

Antifungal fractions and compounds from uncrushed Green Leaves ofAzadirachta indica - G. Suresh; N. S. Narasimhan; S. Masilamani; P. D. Partho; Geetha Gopalakrishnan (Phytoparasitica, 1997)